CD33 and SIGLECL1 Immunoglobulin Superfamily Involved in Dementia. Issue 8 (10th July 2020) - Rendina, Antonella; Drongitis, Denise; Donizetti, Aldo; Fucci, Laura; Milan, Graziella; Tripodi, Francesca; Giustezza, Francesca; Postiglione, Alfredo; Pappatà, Sabina; Ferrari, Raffaele; Bossù, Paola; Angiolillo, Antonella; et al.
Abstract: Sialic acid-binding immunoglobulin-type lectins, which are predominantly expressed in immune cells, represent a family of immunomodulatory receptors with inhibitory and activating signals, in both healthy and disease states. Genetic factors are important in all forms of dementia, especially in early onset dementia. CD33 was recently recognized as a genetic risk factor for Alzheimer disease (AD). Here, we present a 2-generation family with 4 members, the father and the 3 siblings, characterized by an early form of unusual dementia exhibiting a behavioral variant close to behavioral variant frontotemporal dementia phenotype and severe forms of memory loss suggestive of AD. We analyzed the CD33 gene in this family and identified 10 single nucleotide polymorphisms (SNPs) in a linkage disequilibrium block associated with the disease. We also identified a tag SNP, rs2455069-A>G, in CD33 exon 2 that could be involved with dementia risk. Additionally, we excluded the presence of C9orf72 expansion mutations and other mutations previously associated with sporadic FTD and AD. The tag SNP association was also analyzed in selected sporadic AD patients from the same Southern Italy region. We demonstrate that CD33 and SIGLECL1 have a significantly increased level of expression in these patients.